A new high-yield fabrication approach for porous red phosphorus nanosheets using N-methyl-2-pyrrolidone with multiple photocatalytic reduction applications. Issue 14 (1st October 2020) - Zhang, Meili; Liu, Jiaqing; Liu, Lin; Sun, Kailong; Liang, Xiao; Wan, Jun; Fu, Feng
Abstract: In this study, a facile and effective solvothermal treatment-coupled ultrasonic exfoliation strategy was developed to prepare porous red phosphorus nanosheets (RP PNS) with a high yield output. N-methyl-2-pyrrolidone (NMP) was chosen as the dispersant agent to avoid the waste of raw RP materials and to enhance the fragmentation efficiency during the size-reduction process. The BET-specific surface area can reach 84.37 m 2 /g, which is the highest value to date. Additionally, the obtained RP PNS sample exhibits an excellent photocatalytic hydrogen evolution rate of 1169.4 μmol h -1 g -1, a nitrogen fixation rate of 450.4 μmol h -1 g -1, and a 94.3% removal efficiency of 120 mg/L Cr(VI), which are much higher values than those of block RP and micro RP. The enhanced photocatalytic performance can be attributed to the RP PNS sample having a larger specific surface area, more effective mass transfer through the interconnected porous nanosheets, and a higher charge transfer efficiency and carrier density.